Drama out of a crisis: James Connolly's Under Which Flag (1916) and Teresa Deevy's The Wild Goose (1936). Issue 4 (2nd October 2022) - Lusk, Kirsty; Maley, Willy
ABSTRACT: A distinctive strategy of remembrance in Irish historical drama is the depiction of a current crisis through allusion to another traumatic passage in the deep or recent past. In this essay we examine two relatively neglected Irish plays staged twenty years apart which were produced at key moments of reversal and reflection, and which concentrate on female agency, the cyclical Irish curse of betrayal, anxieties of masculinity, and the clash of morality and law. James Connolly's Under Which Flag? (1916) and Teresa Deevy's The Wild Goose (1936) are exemplary instances of how Irish historical drama approaches crisis and commemoration. In each case, by returning respectively to the Fenian Rising of 1867 and events surrounding the Treaty of Limerick of 1691, Connolly and Deevy are able to argue for the continuity of crisis in ways that avoid the fatalism that characterises less nuanced forms of dwelling on and in the past.